A partial nuclear genome of the Jomons who lived 3000 years ago in Fukushima, Japan - Hideaki, Kanzawa-Kiriyama; Kirill, Kyukov; Timothy Adrian, Jinam; Kazuyoshi, Hosomichi; Aiko, Saso; Gen, Suwa; Shintaroh, Ueda; Minoru, Yoneda; Atsushi, Tajima; Ken-ichi, Shinoda; Ituro, Inoue; Naruya, Saitou (Springer Nature, 2017)
The Jomon period of the Japanese Archipelago, characterized by cord-marked ‘jomon’ potteries, has yielded abundant human skeletal remains. However, the genetic origins of the Jomon people and their relationships with modern populations have not been clarified. We determined a total of 115 million base pair nuclear genome sequences from two Jomon individuals (male and female each) from the Sanganji Shell Mound (dated 3000 years before present) with the Jomon-characteristic mitochondrial DNA haplogroup N9b, and compared these nuclear genome sequences with those of worldwide populations. We found that the Jomon population lineage is best considered to have diverged before diversification of present-day East Eurasian populations, with no evidence of gene flow events between the Jomon and other continental populations. This suggests that the Sanganji Jomon people descended from an early phase of population dispersals in East Asia. We also estimated that the modern mainland Japanese inherited <20% of Jomon peoples’ genomes. Our findings, based on the first analysis of Jomon nuclear genome sequence data, firmly demonstrate that the modern mainland Japanese resulted from genetic admixture of the indigenous Jomon people and later migrants.